Quality of sustainability reporting: how is the role of foreign institutional ownership and political connections? - Nuraina, Elva; Narsa, I Made (Opción)
This study aims to investigate the relationship between foreign institutional ownership and the quality of sustainability reporting as a function of political connections. The research sample consists of 485 companies listed on the Indonesian Stock Exchange. The analysis technique used is Generalized Method of Moments (GMM). The results showed that political connections weakened the relationship of foreign institutional ownership and the quality of sustainability reporting. This indicates that higher political connections cause companies to sharply avoid quality sustainability reporting, because sustainability reporting requires their full transparency and disclosure.